Recollections of travel in New Zealand and Australia - Crawford, James Coutts, 1817-1889. (London : Truebner & Co., 1880)
Early traveller reflects on empire, conquests of British race.
Ferguson, J.A. Bibliography of Australia
Keywords: Settlement and contacts - Colonisation - 1788-1850.; Race relations - Racism - Stereotyping; Australia -- Pictorial works; New Zealand -- Description and travel; New Zealand (NZ); Australia